2016
DOI: 10.1186/s10194-016-0688-8
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide-N-Methyltransferase gene rs694539 variant and migraine risk

Abstract: BackgroundMigraine is a common neurovascular disorder affecting 10 to 20 % of the world population usually subdivided into migraine with auro (MA) and migraine without auro (MO). Homocysteine is involved in the pathophysiology of a number of neurological disorders. Elevated levels of homocysteine in the plasma is produced by the MTHFR gene rs 1801133 and rs 1801131 variants as well as the NNMT gene rs 694539 variant.MethodsWith the polymerase chain reaction-restriction fragment length polymorphism method devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…50 Vitamin B6, folic acid and vitamin B12 are required for the metabolism of Hcy (remethylation to methionine requires folic acid and vitamin B12, transsulfuration to cystathionine requires pyridoxine). 51,52 Genetic association studies have already demonstrated a genetic link between enzymes involved in the metabolism of Hcy (namely MTHFR 53 and Nicotinamide-N-Methyltransferase variants 54 ) and migraine, but such a genetic association has not been established for cluster headache 55 or other primary headache disorders. 56 In the present study, a systematic search of the literature with regard to the supplementation of Hcy-lowering vitamins for migraine and other primary headache disorders was performed.…”
Section: Discussionmentioning
confidence: 99%
“…50 Vitamin B6, folic acid and vitamin B12 are required for the metabolism of Hcy (remethylation to methionine requires folic acid and vitamin B12, transsulfuration to cystathionine requires pyridoxine). 51,52 Genetic association studies have already demonstrated a genetic link between enzymes involved in the metabolism of Hcy (namely MTHFR 53 and Nicotinamide-N-Methyltransferase variants 54 ) and migraine, but such a genetic association has not been established for cluster headache 55 or other primary headache disorders. 56 In the present study, a systematic search of the literature with regard to the supplementation of Hcy-lowering vitamins for migraine and other primary headache disorders was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Sazci et al report that previous studies showed an association between methylenetetrahydrofolate reductase (MTHFR) variants C677T (rs1801133), A1298C (rs1801131) and migraine (110). Furthermore, the nicotinamide-N-methyltransferase (NNMT) variant rs694539, expressed in the brain and other nervous tissue as a cytoplasmic enzyme, was associated with migraine presence (110). The implicated MTHFR variants and the NNMT variant have been linked to higher plasma homocysteine levels, which, in turn, have been associated with migraine risk (110).…”
Section: Genetics and Biomarkersmentioning
confidence: 99%
“…Furthermore, the nicotinamide-N-methyltransferase (NNMT) variant rs694539, expressed in the brain and other nervous tissue as a cytoplasmic enzyme, was associated with migraine presence (110). The implicated MTHFR variants and the NNMT variant have been linked to higher plasma homocysteine levels, which, in turn, have been associated with migraine risk (110). However, the association between the NNMT variant and migraine was only found in women, with 4.3 times the odds for women with an AA genotype and the same magnitude of protective effect in individuals with the G allele (110).…”
Section: Genetics and Biomarkersmentioning
confidence: 99%
“… 19 Sazci et al reported a significant association of the NNMT rs694539 variant with female patients with migraine, but no association with male patients. 47 CoSkun et al suggested that the genotypes rs2229741-GG and rs726281-GG are responsible for reduced risk of migraine in female Turkish patients. 48 Dopamine signaling was demonstrated to be linked to the female hormones, namely, progesterone and prolactin, in the migraineurs.…”
Section: Discussionmentioning
confidence: 99%